Inter-Country COVID-19 Contagiousness Variation in Eight African Countries - Singini, Geoffrey Chiyuzga; Manda, Samuel O. M. (Frontiers in Public Health, 2022)
The COVID-19 pandemic is exerting great strain on the already fragile and weak economies, health and education systems of all countries in the Africa continent. Although, countries in Africa continent were expected to be hardest hit by the COVID-19 pandemic, they have unexpectedly attained low COVID-19 infections. Nonetheless, due to the varied economic, health systems, and social strengths and vulnerabilities, the pandemic is affecting African countries differently. In this paper, we used Susceptible, Infectious, or Recovered (SIR) mathematical models to predict reproduction numbers, contact rate, removal rate, and infectious period of the COVID-19 pandemic in eight Africa countries, namely Angola, Botswana, Egypt, Ethiopia, Malawi, Nigeria, South Africa, and Tunisia as at end of July 2021. Our analysis and results could assist in providing a broader coverage of past, current, and future prediction of the COVID-19 situations across Africa, which would help policy makers towards evidence-based decisions.